Identification of Site Vulnerabilities Using Refraction Microtremor (REMI) Method in Sambelia District of East Lombok - Mardatillah, Mardatillah; Syamsuddin, Syamsuddin; Rahmatun Inayah; Ika Umratul Asni Aminy; Adella Ulyandana Jayatri (Frontier Advances in Applied Science and Engineering, 2025)
Research on site vulnerability identification using the Refraction Microtremor (ReMi) method has been conducted in Sambelia District, East Lombok regency. The purpose of this study was to identify the vulnerability of the soil in the study area by determining the lithology of subsurface rocks. Measurement of Microtremor Refraction (ReMi) was carried out at 16 points spread over the study area. Data processing to obtain 1D shear wave velocity profile using McSEIS seisimager surface wave analysis wizard. Based on the research that has been done, four layers of rock are obtained, namely the first layer with a value of Vs 466-543 m/s in the form of clay at a depth of (0-6.0 m), the second layer with a value of Vs 429-668 m/s in the form of solid sand and gravel at a depth of (6.0-16.1 m), the third layer with a value of Vs 726-812 m/s in the form of breccia at a depth of (16.1 - 18.6 m), and the fourth layer with a value of Vs 905-1454 m/s identified as the Tuff is at a depth of (18.6 – 30.0 m). The conclusion of this study is that Belanting and Sugian villages have a high level of vulnerability because they are dominated by very dense soils and soft rocks (Type C) with constituent rocks, namely alluvial rocks (solid sand, gravel, clay, and silt) and Darakunci village has a low level of vulnerability composed of breccia and Tuff rocks.